Rancang Bangun Pengendali Katup Solenoid Otomatis Melalui PC Pada Kalibrator Laju Aliran Air Piston Prover OT-400 - Prakosa, Jalu Ahmad; Sirenden, Bernadus Herdi (INKOM Journal, 2011)
<!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; font-size:11.0pt; mso-bidi-font-size:10.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.AbstractKeywords, li.AbstractKeywords, div.AbstractKeywords {mso-style-name:"Abstract Keywords"; mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:"Abstract Text"; margin:0in; margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; font-style:italic; mso-bidi-font-style:normal;} p.AbstractText, li.AbstractText, div.AbstractText {mso-style-name:"Abstract Text"; mso-style-unhide:no; margin:0in; margin-bottom:.0001pt; text-align:justify; text-indent:.5in; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; font-style:italic; mso-bidi-font-style:normal;} p.AbstractTitle, li.AbstractTitle, div.AbstractTitle {mso-style-name:"Abstract Title"; mso-style-unhide:no; margin-top:12.0pt; margin-right:0in; margin-bottom:6.0pt; margin-left:0in; text-align:center; mso-pagination:widow-orphan; font-size:11.0pt; mso-bidi-font-size:10.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; font-weight:bold; mso-bidi-font-weight:normal;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> Abstract Designing and creating of automatic solenoid valve of control circuit through the Personal Comupter (PC) on  water flow rate calibration system piston prover OT-400 has been done at the fluid flow laboratory of  Research Center for Calibration, Instrumentation and Metrology LIPI. Solenoid is used to control the water flow rate by adjusting the opening and closing its valve. ATmega328 microcontroller on the Arduino Duemilanove board is used to control the input voltage solenoid by using Pulse Width Modulation (PWM) and communicates serially via the PC with USB port. From the test results found that these control systems can run well in controlling the solenoid valve, so that research activities in analyzing the solenoid valve to control water flow rate can be done more easily, quickly and efficiently.   Keywords: control, solenoid valve, Arduino Duemilanove, water flow rate. Abstrak Telah dilakukan perancangan dan pembuatan rangkaian pengendali katup solenoid otomatis melalui Personal Comupter(PC) pada sistem kalibrasi laju aliran air piston prover OT-400 di laboratorium aliran fluida  Pusat Penelitian Kalibrasi, Instrumentasi dan Metrologi LIPI. Solenoid ini digunakan untuk mengendalikan laju aliran air dengan mengatur buka tutup katupnya. Digunakan mikrokontroler ATmega328 pada board arduino Duemilanove untuk mengendalikan tegangan input solenoid dengan menggunakan Pulse Width Modulation(PWM) dan berkomunikasi serial dengan PC melaui port USB. Dari hasil pengujian didapatkan bahwa sistem pengendali ini dapat berjalan dengan baik dalam mengendalikan katup solenoid, sehingga kegiatan penelitian dalam menganalisa pengendalian katup solenoid terhadap laju aliran air dapat dilakukan dengan lebih mudah, cepat dan efisien.   Kata kunci: kendali, katup solenoid, Arduino Duemilanove, laju aliran air.